Functional activity of peripheral blood eosinophils in allergen-induced late-phase airway inflammation in asthma patients - Lavinskiene, Simona (J Inflamm (Lond), 2015)
OBJECTIVE: We aimed to investigate peripheral blood eosinophil chemotaxis, generation of spontaneous reactive oxygen species (ROS), and apoptosis in patients with allergic asthma after bronchial allergen challenge. MATERIAL AND METHODS: A total of 18 patients with allergic asthma (AA), 14 with allergic rhinitis (AR), and 10 healthy subjects (HS) underwent bronchial challenge with a specific allergen extract. Eosinophils from peripheral blood were isolated 24 h before as well as 7 and 24 h after bronchial allergen challenge. Chemotaxis, spontaneous ROS production in eosinophils, and apoptosis were analyzed by flow cytometry. Serum and induced sputum IL-5 levels were measured by ELISA; the cell count in sputum was analyzed by the May-Grünwald-Giemsa method. RESULTS: Before bronchial allergen challenge, peripheral blood eosinophil chemotaxis, spontaneous ROS production was enhanced and eosinophil apoptosis was reduced in the patients with AA as compared with AR patients and HS (P < 0.05). Meanwhile, eosinophil chemotaxis and ROS generation markedly increased in the patients with AA 7 h and 24 h after challenge compared with other groups and baseline values (P < 0.05). The percentage of apoptotic eosinophils in the patients with AA decreased at 7 h as well as 24 h after challenge when compared with other groups and the baseline values (P < 0.05). There was a significant correlation between the migrated peripheral blood eosinophil count and the sputum eosinophil count (Rs = 0.89, P < 0.0001) and the sputum IL-5 level (Rs = 0.68, P = 0.002) at 24 h after bronchial challenge only in the patients with AA. Furthermore, the percentage of peripheral blood apoptotic eosinophils significantly correlated with eosinophil count in sputum (Rs = −0.53, P = 0.02), and ROS production correlated with the serum IL-5 levels (Rs = 0.71, P = 0.01). CONCLUSION: During allergen-induced late-phase airway inflammation, peripheral blood eosinophils demonstrated further alterations of their functional activity manifested by enhanced spontaneous ROS production, increased chemotaxis, and diminished apoptosis in patients with AA.